Diversity of oligodendrocytes and their progenitors. (December 2017) - Dimou, Leda; Simons, Mikael
Highlights: OPCs are heterogeneous under physiological and pathological conditions. Oligodendrocytes have functions beyond saltatory nerve conduction. Adult glia remain in a plastic state thereby enabling their conversion into new states. Oligodendroglia are susceptible to various neurological and psychiatric diseases. Abstract : The established function of oligodendrocytes and their progenitors is to drive the cellular events of myelination, a highly diversified process necessary to match the needs of various neuronal subtypes and networks. The morphological and molecular heterogeneity of oligodendrocytes and their progenitors point to functions beyond establishing saltatory nerve conduction. Here, we review the diversity in the oligodendroglial lineage as well as the classical and new functions identified for oligodendrocytes and their progenitors. Because oligodendroglia remain highly responsive to environmental changes, they likely contribute to various neurological and psychiatric diseases.